Exports- and imports-led growth: Evidence from a time series analysis, case of Jordan - Rasha Istaiteyeh; Farah Najem; Nahil Ismail Saqfalhait (Economies, 2023)
The purpose of this study is to examine equilibrium relationships and dynamic causality between economic growth (measured as GDP), exports, and imports in Jordan using time-series data between 1976 and 2021. In particular, this research attempts to determine exports-led growth, imports-led growth, growth-led exports, and growth-led imports in both the short-run and long-run. The four time-series datasets, GDP, merchandise exports, merchandise imports, and gross capital formation, were examined using the Dickey-Fuller unit root tests, the Phillips-Perron unit root test, and the Johansen's trace tests for cointegration. The dynamic properties of the VAR(1) were summarized using Granger causality tests and impulse response functions. The test results showed that the impulse response functions indicated that there might be some short-run relationships among our datasets. The Johansen cointegration tests suggested that the series were not cointegrated, and hence there were no long-term relationships among the time series. It appeared that in the short-run, both GDP and gross capital formation Grangerly caused merchandise exports. A unit shock in merchandise exports, merchandise imports, and gross capital formation caused very small fluctuating responses from GDP, merchandise exports, merchandise imports, and gross capital in the short-run, and the responses approached zero in the long-run.
Keywords: 330; Jordan; exports; imports; economic growth; causality